"You Cannot Make Friends at Work"? Relatedness in and beyond the Workplace and the Reconfiguration of Kinship and Gender in Urban China. (November 2022) - Peng, Xinyan
Based on ethnographic fieldwork conducted in the form of immersive research in corporate Shanghai, this article demonstrates how white-collar women in urban China crafted relatedness in the interstitial times and spaces of and beyond the workplace. It brings to light how the precarious nature of work and the workplace environment shaped the precarious nature of relatedness established by those women who worked together. Though aware of the assumed lack of sociability and interpersonal trust as well as the fleeting and momentary ties formed in urban and corporate spaces defined by mobility and instability, white-collar women who worked together developed ties of relatedness to express their own desired understanding of the self and familial and gender roles. Forms of relatedness produced among white-collar women in and beyond the workplace occupy a space between home and work, reconceptualize women's roles and places in family life, and reconfigure kinship and gender.